EXPERIMENT STUDY ON MECHANICAL PROPERTY OF TITANIUM ALLOY TC11 BY 3D LASER RAPID PROTOTYPING - WANG XinBo; QIN JianBo; TAN ShenGang (Jixie qiangdu)
Through the experiments on mechanical properties of TC11 titanium alloy by 3D laser rapid prototyping,obtained the performance data of static tension,S-N curve,DFR value,and fracture toughness. Furthermore,compared and analyzed the TC18 and TC21 performance data. The results show that the comprehensive properties of TC11 laser forming titanium alloy are basically between TC21 and TC18. The defects of the internal defects such as non fusion or air bubble have great influence on the fatigue properties,and the follow-up needs to continue to improve the manufacturing process and reduce the internal defects,which can be controlled and ensure the safety of aircraft.